Potensi Tanaman Pekarangan sebagai Tanaman Refugia - Ni Luh Eka Savitri; Bagyo Yanuwiadi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study focuses on the potential of yard plants as refugia plants that play an important role in maintaining the balance of the ecosystem in residential areas. Yard plants not only function as aesthetic elements that beautify the environment, but also play an ecological role as providers of microhabitats for various organisms, including natural enemies of plant pests. In the context of applied ecology, the concept of refugia emphasizes the function of certain plants that can provide shelter, food sources, and reproductive areas for predators and parasitoids that play a role in biological control of pests. Therefore, the identification and analysis of the potential of yard plants as refugia are important to support the principle of sustainable environmental management in residential areas. This study aims to analyze the composition and structure of yard plant vegetation, identify the main types of arthropod visitors to dominant plants, and assess the ecological relationship between vegetation and the presence of arthropods. The research methods include vegetation surveys with direct censuses to determine the types and dominance of plants, and observations of arthropods using visual encounter techniques. Data were analyzed descriptively quantitatively to determine the structure of the vegetation community and the intensity of interactions between biotic components. The results showed that the most common types of yard plants were the Lily (Hymenocallis littoralis) and the Balinese Ornamental Pandanus (Dracaena draco), with the highest visitation rate among arthropods in the Formicidae family. These findings demonstrate the ecological potential of yard plants as supporting elements for the conservation of natural enemies of pests. This study emphasizes the importance of optimizing yard vegetation as refugia plants to support biological control systems and increase public awareness of the ecological function of plants in the residential environment.